2019
DOI: 10.31413/nativa.v7i5.7206
|View full text |Cite
|
Sign up to set email alerts
|

Manejo Da Palhada E Adubação Na Produção Da Soja E Cobertura Do Solo

Abstract: Diversos fatores podem interferir no desenvolvimento da cultura da soja, dentre os quais pode-se citar o manejo de restos culturais e o método de aplicação do adubo. Assim, objetivou-se avaliar os equipamentos de manejo da palhada (rolo-faca, triturador de palhas e roçadora) e sistemas de adubação (em pré-semeadura e na semeadura), na produção da soja e cobertura do solo. O experimento foi conduzido em Latossolo Vermelho utilizando-se um esquema fatorial 2 x 3 em blocos casualizados com quatro repetições. Fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Carvalho et al (2004) studied soybean in succession to green manure under no-tillage and conventional planting systems in the Cerrado region and also obtained an absence of interference of the green manure in the thousand-grain weight in two agricultural years of experimentation. Garcia et al (2014), Cortez et al (2019), andGuera, Fonseca, andHarkatin (2020) also found comparable results of non-interference of early fertilization.…”
Section: Resultsmentioning
confidence: 73%
“…Carvalho et al (2004) studied soybean in succession to green manure under no-tillage and conventional planting systems in the Cerrado region and also obtained an absence of interference of the green manure in the thousand-grain weight in two agricultural years of experimentation. Garcia et al (2014), Cortez et al (2019), andGuera, Fonseca, andHarkatin (2020) also found comparable results of non-interference of early fertilization.…”
Section: Resultsmentioning
confidence: 73%
“…This result may have been influenced by the existing straw in the soil resulting from the cultivation of previous crops (soybean, maize, and wheat) in the no-tillage system running for 6 harvesting cycles. The cover residues favor soil moisture retention, promoting better conditions for crop germination and emergence (Cortez et al, 2019). Treatments: T1 -Control; T2 -Mineral fertilization with 300 kg ha -1 of formulated 00-30-10; T3 -27.20 kg of filter cake; T4 -54.40 kg of filter cake; T5 -81.60 kg of filter cake; T6 -108.80 kg of filter cake.…”
Section: Resultsmentioning
confidence: 99%